Food security in welfare capitalism: Comparing social entitlements to food in Australia and Norway. (February 2016) - Richards, Carol; Kjærnes, Unni; Vik, Jostein
Abstract: The concept of food security is often anchored in popular understandings of the challenge to produce and supply enough food. However, decades of policies for intensive agriculture have not alleviated hunger and malnutrition, with an absence of food security featuring in both economically developing and developed nations. Despite perceptions that the economic growth in advanced, capitalist societies will ensure freedom from hunger, this is not universal across so-called 'wealthy nations'. To explore the dynamics of food security in economically developed countries, this paper considers institutional approaches to domestic food security primarily through responses to poverty and welfare entitlements, and, secondarily, through food relief. Through the lens of social entitlements to food and their formation under various expressions of welfare capitalism, we highlight how the specific institutional settings of two economically developed nations, Australia and Norway, respond to uncertain or insufficient access to food. Whilst Norway's political agenda on agricultural support, food pricing regulation and universal social security support offers a robust, although indirect, safety net in ensuring entitlements to food, Australia's neoliberal trajectory means that approaches to food security are ad hoc and rely on a combination of self-help, charitable and market responses. Despite its extensive food production Australia appears less capable of ensuring food security for all its inhabitants compared to the highly import-dependent Norway. Highlights: Household level food security is not universal across wealthy nations. Those experiencing poverty are highly vulnerable to hunger. This study of Australia and Norway highlights how different forms of welfare capitalism addresses poverty and social entitlements to food. Norway's social democratic agenda protects its citizens from poverty, indirectly maintaining access to food as a universal entitlement. Australia's (neo)liberalised welfare state necessitates individual self-help, charitable and market responses to address poverty and hunger.